Redundancy, Feedback, and Robustness in the Arabidopsis thaliana BZR/BEH Gene Family - Lachowiec, Jennifer; Mason, G. Alex; Schultz, Karla; Queitsch, Christine (Frontiers in Genetics, 2018)
Organismal development is remarkably robust, tolerating stochastic errors to produce consistent, so-called canalized adult phenotypes. The mechanistic underpinnings of developmental robustness are poorly understood, but recent studies implicate certain features of genetic networks such as functional redundancy, connectivity, and feedback. Here, we examine the BZR/BEH gene family, whose function contributes to embryonic stem development in the plant Arabidopsis thaliana, to test current assumptions on functional redundancy and trait robustness. Our analyses of BZR/BEH gene mutants and mutant combinations revealed that functional redundancy among these gene family members is not necessary for trait robustness. Connectivity is another commonly cited determinant of robustness. Although our results do not suffice to fully exclude connectivity as a cause of robustness within the BZR/BEH gene family, our analyses of gene expression and motifs in regulatory regions found no correlation between connectivity among gene family members or their connectivity with other transcription factors and effects on developmental robustness. Instead, our data suggest that BEH4, the earliest diverged family member, modulates developmental robustness. We present evidence indicating that regulatory cross-talk among gene family members is integrated by BEH4 to promote wild-type levels of developmental robustness. Further, the chaperone HSP90, a known determinant of developmental robustness, appears to act via BEH4 in maintaining robustness of embryonic stem length. In summary, we demonstrate that even among closely related transcription factors, trait robustness can arise through the activity of a single gene family member, challenging common assumptions about the molecular underpinnings of robustness.